2012
DOI: 10.1111/j.1748-5827.2012.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, blood gas and acid–base values in the Galgo Español (Spanish greyhound)

Abstract: These results confirm that significant haematologic differences exist in Galgos Españoles when compared with other dogs, although these differences are not as striking as in greyhounds. Practitioners need to be aware of these breed-specific differences in order to make accurate diagnoses in Galgos Españoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…Haematological and serum biochemical data for Spanish greyhounds (Galgos) have recently been reported. Similar to greyhounds, Galgos had higher Hct, Hb concentration and RBC count and lower platelet counts than dogs in general (Mesa-Sanchez et al 2012).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Haematological and serum biochemical data for Spanish greyhounds (Galgos) have recently been reported. Similar to greyhounds, Galgos had higher Hct, Hb concentration and RBC count and lower platelet counts than dogs in general (Mesa-Sanchez et al 2012).…”
Section: Resultsmentioning
confidence: 78%
“…Similar to greyhounds, Galgos had higher Hct, Hb concentration and RBC count and lower platelet counts than dogs in general (Mesa‐Sanchez et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…15,16 The prevalence of DEA 1 has already been shown 592025V DIXXX10.1177/1040638715592025Blood types DEA 1, 4, and 7 in galgosSpada et al…”
mentioning
confidence: 98%
“…However, recent studies suggest that each sighthound breed presents its own specific laboratory features, and the extrapolation of Greyhound clinicopathological information to other sighthounds could lead to misdiagnoses (Uhrikova et al 2013;Sheerer et al 2013;Mesa-Sanchez et al 2014). Previous studies have shown that Galgos have similar haematological values than those found in Greyhounds (MesaSanchez et al 2012); however, they have different electrolyte concentrations, blood gas values, acid-base balance and prevalence of dog erithrocyte antigen 1.1, compared with those previously described in Greyhounds (Mesa-Sanchez et al 2012, 2014. Interestingly, Galgos also have slightly higher haptoglobin concentration than the general population of dogs, in contrast to Greyhounds, which have undetectable haptoglobin levels (Zaldívar-López et al 2012).…”
Section: Introductionmentioning
confidence: 70%